Swamy's master guide FR & SR service rules and financial rules - Muthuswamy; Sanjeev (Chennai Swamy, 2023)
The Controller-General of Accounts has prescribed (1) Leave Travel Concession Scheme for Central Government Employees, (ii) General Provident Fund (Central Services) Rules, 1960, and (iii) CCS (CCA) Rules, 1965, in the syllabus for the recruitment examination of Junior Accounts Officers (Civil). General Financial Rules, Conduct Rules, CEA Rules, RTI Rules, etc.
Keywords: Financial rules